2017
DOI: 10.2147/ott.s126075
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory cohort study and meta-analysis of <em>BIM</em> deletion polymorphism in patients with epidermal growth factor receptor-mutant non-small-cell lung cancer treated with epidermal growth factor receptor tyrosine kinase inhibitors

Abstract: BackgroundNon-small-cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations might develop primary and secondary resistance to tyrosine kinase inhibitors (TKIs). The proapoptotic protein Bcl-2-like 11 (BIM) is a key modulator of apoptosis triggered by EGFR-TKIs. The recent studies have indicated that some patients with positive EGFR mutations were refractory to EGFR-TKIs if they harbored a BIM deletion polymorphism. The purpose of this study was to investigate whether BIM polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Therefore, the conclusions made by these meta-analyses should be interpreted cautiously. Since more original studies in this area have been published in recent 3 years, [ 17 20 , 23 , 24 ] we conducted this updated meta-analysis to obtain an objective and consistent conclusion. To the best of our knowledge, this updated meta-analysis collected the comprehensive literature and was more accurate as the heterogeneity in the analysis was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the conclusions made by these meta-analyses should be interpreted cautiously. Since more original studies in this area have been published in recent 3 years, [ 17 20 , 23 , 24 ] we conducted this updated meta-analysis to obtain an objective and consistent conclusion. To the best of our knowledge, this updated meta-analysis collected the comprehensive literature and was more accurate as the heterogeneity in the analysis was low.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that NSCLC patients harboring BIM deletion polymorphism had inferior response to EGFR-TKIs than those with BIM wild after TKIs treatment, [ 11 20 ] while others argued that there was no difference in response to EGFR-TKIs in NSCLC patients with and without BIM deletion polymorphism. [ 21 24 ]…”
Section: Introductionmentioning
confidence: 99%
“…For two studies, each reported two unrelated cohorts [21,23]. Finally, 20 datasets from 18 studies [18][19][20][21][22][23][35][36][37][38][39][40][41][42][43][44][45][46] exploring the association between BIM deletion polymorphism and EGFR-TKI efficacy in EGFR-mutant NSCLC patients were included in our meta-analysis (Figure 1).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Others found that EGFR-mutant patients with and without the BIM deletion polymorphism had similar clinical outcomes in response to EGFR-TKI treatment (165)(166)(167)(168). Several meta-analyses have indicated that the BIM deletion polymorphism is associated with poor ORR (168)(169)(170)(171)(172), consistent with other studies demonstrating that the BIM deletion polymorphism is associated with shorter PFS in patients with NSCLC harboring EGFR mutations who received EGFR-TKIs (168)(169)(170)(171)(172)(173)(174)(175). Only one study showed no significant association between BIM status and the response to EGFR-TKIs (173).…”
Section: Bim Polymorphismmentioning
confidence: 99%
“…Some studies have shown that EGFR-mutant NSCLC patients with the BIM deletion polymorphism had inferior EGFR-TKI efficacy compared to those with wild-type BIM ( 154 , 160 – 164 ). Others found that EGFR-mutant patients with and without the BIM deletion polymorphism had similar clinical outcomes in response to EGFR-TKI treatment ( 165 168 ). Several meta-analyses have indicated that the BIM deletion polymorphism is associated with poor ORR ( 168 172 ), consistent with other studies demonstrating that the BIM deletion polymorphism is associated with shorter PFS in patients with NSCLC harboring EGFR mutations who received EGFR-TKIs ( 168 175 ).…”
Section: Other Biomarkersmentioning
confidence: 99%